Catenulisporidins A and B, 16-membered macrolides of the hygrolidin family produced by the chemically underexplored actinobacterium Catenulispora species. Issue 7 (1st April 2020) - Son, Sangkeun; Jang, Mina; Lee, Byeongsan; Lee, Jung-Sook; Hong, Young-Soo; Kim, Bo Yeon; Ko, Sung-Kyun; Jang, Jae-Hyuk; Ahn, Jong Seog
Graphical abstract: Abstract: Two new macrolide metabolites of the hygrolidin family, catenulisporidins A and B (1 and 2 ), together with a known compound hygrolidin (3 ), were isolated from the culture broth of the rare actinobacterium Catenulispora sp. KCB13F192. Their structures were elucidated on the basis of HRESIMS spectrometric and NMR spectroscopic analyses. Catenulisporidins A and B are the first example of natural hygrolidin and bafilomycin derivatives featuring a modified macrolide ring, and catenulisporidin A possesses a tetrahydrofuran ring through an ether linkage between C-7 and C-10. In cell-based fluorescent imaging and immunoblot assays, the three compounds were shown to inhibit autophagic flux in HeLa cells.